1988
DOI: 10.1126/science.2834822
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Lysine-Containing Zeins into Protein Bodies in Xenopus Oocytes

Abstract: Zeins, the storage proteins of maize, are totally lacking in the essential amino acids lysine and tryptophan. Lysine codons and lysine- and tryptophan-encoding oligonucleotides were introduced at several positions into a 19-kilodalton zein complementary DNA by oligonucleotide-mediated mutagenesis. A 450-base pair open reading frame from a simian virus 40 (SV40) coat protein was also engineered into the zein coding region. Messenger RNAs for the modified zeins were synthesized in vitro with an SP6 RNA polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…The proteases were incubated in the presence or absence of Triton X-100, which removes the RER membrane surrounding the protein body (22). In the absence of detergent, the 27-kD y-zein was not detected after a 4-h incubation, but the a-zeins remained relatively stable throughout the 24-h period (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proteases were incubated in the presence or absence of Triton X-100, which removes the RER membrane surrounding the protein body (22). In the absence of detergent, the 27-kD y-zein was not detected after a 4-h incubation, but the a-zeins remained relatively stable throughout the 24-h period (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of protein bodies in maize is speculated to be partly related to the intrinsic structure of the prolamins. ␣-Zein expressed in Xenopus oocytes was shown to be assembled into protein body-like structures (22). However, the expression of only ␣-zein resulted in the formation of low-density protein bodies, which suggested that all prolamins are necessary for synthesis of normal protein bodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, a-zein can form protein bodies by itself in frog oocytes (Wallace et al, 1988). In maize endosperm, protein bodies are first initiated by the B 5 1000 Figure 9.…”
Section: Discussionmentioning
confidence: 99%